Using flexible customer pricing strategies in the B2C market for vegetable products: Menggunakan strategi penetapan harga pelanggan yang fleksibel di pasar B2C untuk produk sayuran - Sharipov Ikhtiyor (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article examines the role of price in the vegetable market. Directions for using flexible pricing strategies are based on the customer in the B2C market of vegetable products